2007
DOI: 10.1016/j.cellimm.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin-induced cytokine differentiation and clonal expansion of T cells is mediated predominantly via costimulation

Abstract: Pertussis toxin (PTX) has potent immunologic adjuvant activity in vivo and concomitantly enhances both T helper type (Th) 1 and Th2 cytokine responses. The PTX-induced enhancement of Th1 and Th2 immunity is mediated via the activation of antigen presenting cells (APCs), but the underlying mechanism is not known.Here we asked whether the adjuvant activity of PTX on T cell immunity was mediated by cytokines and/or costimulatory signals.The results show that in vivo blockade of CD28-CD80/86 costimulation essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The upregulation of CD28 on CD8+ T cells by PTX suggested that the CD80/86 pathway could play a role, similar to previous observations with CD4+ T cells [16]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The upregulation of CD28 on CD8+ T cells by PTX suggested that the CD80/86 pathway could play a role, similar to previous observations with CD4+ T cells [16]. …”
Section: Resultssupporting
confidence: 88%
“…Several studies showed that it activates APCs and upregulates CD80, CD86, and MHC class II molecules, suggesting that its effects on T cells are mediated indirectly [14]. Along these lines, Wakatsuki and colleagues provided evidence that PTX bound to APCs was critical for its T cell activating properties, and Denkinger and colleagues showed that PTX-induced clonal expansion and cytokine differentiation of Th1 and Th2 cells was primarily dependent on costimulation via CD80/86 molecules [15;16]. However, some studies have suggested a direct effect of PTX on T cells [17;18], and it is conceivable that modulation of CD28 and/or CTLA-4 expression on T cells could contribute to the PTX adjuvant activity.…”
Section: Introductionmentioning
confidence: 99%
“…vascular endothelial cells) resulting in the subsequent activation of CD4 + T cells and death of the animals. This view is consistent with studies showing a direct effect of PTX on APCs leading to the upregulation of costimulatory molecules and enhanced cytokine production (35,36,40). …”
Section: Discussionsupporting
confidence: 92%
“…PTX also enhances the ability of the APC to activate T cells by inducing dendritic cell maturation (62) and up-regulating expression of the co-stimulatory molecules CD80 and CD86 in the spleen and spinal cord (40, 41, 63). PTX-induced cytokine production and T cell clonal expansion are thought to occur primarily through the CD28:CD80/86 costimulatory pathway (64). The PTX-induced changes in EAE susceptibility of B10.D1 mice cannot be attributed solely to effects on either T cells or APCs based on these experiments.…”
Section: Discussionmentioning
confidence: 99%